Effects of dexamethasone and meloxicam on Borrelia burgdorferi-induced inflammation in glial and neuronal cells of the central nervous system. Issue 1 (December 2017) - Ramesh, Geeta; Martinez, Alejandra; Martin, Dale; Philipp, Mario
Abstract Background Lyme neuroborreliosis (LNB), caused by the spirocheteBorrelia burgdorferi (Bb), affects both the central and peripheral nervous systems. Previously, we reported that in a model of acute LNB in rhesus monkeys, treatment with the anti-inflammatory drug dexamethasone significantly reduced both pleocytosis and levels of cerebrospinal fluid (CSF) immune mediators that were induced by Bb. Dexamethasone also inhibited the formation of inflammatory, neurodegenerative, and demyelinating lesions in the brain and spinal cord of these animals. In contrast, these signs were evident in the infected animals that were left untreated or in those that were treated with meloxicam, a non-steroidal anti-inflammatory drug. Methods To address the differential anti-inflammatory effects of dexamethasone and meloxicam in the central nervous system (CNS), we evaluated the potential of these drugs to alter the levels of Bb-induced inflammatory mediators in culture supernatants of rhesus frontal cortex (FC) explants, primary rhesus astrocytes and microglia, and human oligodendrocytes. We also ascertained the potential of dexamethasone to modulate Bb-induced apoptosis in rhesus FC explants. As meloxicam is a known COX-2 inhibitor, we evaluated whether meloxicam altered the levels of COX-2 as induced by live Bb in cell lysates of primary rhesus astrocytes and microglia. Results Dexamethasone but not meloxicam significantly reduced the levels of several Bb-induced immune mediators in culture supernatants of FC explants, astrocytes, microglia, and oligodendrocytes. Dexamethasone also had a protective effect on Bb-induced neuronal and oligodendrocyte apoptosis in rhesus FC explants. Further, meloxicam significantly reduced the levels of Bb-induced COX-2 in microglia, while both Bb and meloxicam were unable to alter the constitutive levels of COX-2 in astrocytes. Conclusions These data indicate that dexamethasone and meloxicam have differential anti-inflammatory effects on Bb-induced inflammation in glial and neuronal cells of the CNS and help explain the in vivo findings of significantly reduced inflammatory mediators in the CSF and lack of inflammatory neurodegenerative lesions in the brain and spinal cord of Bb-infected animals that were treated with dexamethasone but not meloxicam. Signaling cascades altered by dexamethasone could serve as possible therapeutic targets for limiting CNS inflammation and tissue damage in LNB.